Assessment of effect of different sterilization agents on dimensional accuracy of different impression materials in implant prosthesis - An In vitro study - Kumari Kavita; K R Parameshwar Reddy; K R Maheshwar Reddy; Swatantra Kumar; Gyanendra Pandey; Revati Singh (Wolters Kluwer Medknow Publications, 2021)
Aim: Sterilization of impression materials is of paramount importance. The present study was conducted to compare the effect of different disinfectants on dimensional accuracy of elastomeric impression materials used for implant prosthesis and other routine treatments. Materials and Methods: The present study was conducted with polyvinyl siloxane (PVS) (regular body), PVS (medium body), PVS (heavy body), and polyether (medium body) impression materials. Glutaraldehyde (2%) and sodium hypochlorite (NaOCl, 0.525%) were the disinfectant solutions employed in the study. After 16 h, the specimens were measured under Leica WILD stereomicroscope and dimensions were compared with master die. Results: The dimensional change in the Controls, 2% glutaraldehyde (Group I), and 0.525% NaOCl (Group II) was non significant where as Group III and Group IV showed statistically significant difference (P < 0.05). Results also showed significantly higher tear strength (newton/millimeter) in Control group followed by Group I and Group II. Conclusion: PVS (heavy body) was found to be most stable, and polyether was seen to be stable of all the impression materials.